Chondrosarcomas in children and adolescents. Issue 2 (3rd February 2020) - Puri, Ajay
Abstract : Chondrosarcomas in children and adolescents are uncommon and constitute < 5% of all chondrosarcomas. There are very few studies discussing extremity chondrosarcomas in young patients. The pelvis is the most common site, followed by the proximal femur. As cartilaginous tumours can be quite challenging to diagnose, it is best for these lesions to be discussed in a multidisciplinary meeting which includes a radiologist and a pathologist specializing in bone tumours. Treatment principles are similar to those in adults, with adequate surgical excision respecting oncologic principles being the mainstay of treatment. Select extremity Grade I chondrosarcomas may be managed with extended intralesional curettage without increasing the risk for local recurrence or metastatic disease, but case selection is critical and should be based on clinical, imaging and histological characteristics. Chondrosarcomas are resistant to chemotherapy and relatively radioresistant. For mesenchymal chondrosarcomas, there may be a role for chemotherapy, though data on this is limited. Prognosis and rate of recurrence correlate directly to the adequacy of the surgical resection. Chondrosarcomas in younger patients behave in a similar fashion to those in adults, and outcomes in the young are no different from those in adults. Cite this article: EFORT Open Rev 2020;5:90-95. DOI: 10.1302/2058-5241.5.190052